Challenging the Biomedical Notion of ‘Active Substance’: The Botanical Plasticity of Tibetan Medical Formulas (HIMALAYA, 2023)
Sowa Rigpa (Tibetan medicine) has been practiced across vast regions of Central and South Asia for centuries. In this medical tradition, it is common practice to dynamically adapt the mainly herbal formulas according to the regional flora and local conditions, and to use local variants of ingredients. Consequently, one Tibetan ingredient name within a specific formula can signify a variety of therapeutically fitting botanical items, which appear quite different from the perspective of modern taxonomy. This has led many researchers to understand the botanical plasticity of Tibetan medical formulas as misidentifications. We develop an alternative approach, exploring the advantages of this plasticity as a necessary practice to fulfill economic and therapeutic needs. This perspective piece questions the biomedical paradigm of single ‘active substances,’ since botanically unrelated plants with different chemical compositions can be similarly therapeutically effective. From a systems biology perspective, network pharmacology lets us understand the correspondence of illness and medicine as a semiotic process in which herbal formulations act via their ‘pleiotropic signatures’: complex webs of signal pathways that connect and act on multiple levels of organization in the body.